1999
DOI: 10.1063/1.370518
|View full text |Cite
|
Sign up to set email alerts
|

Porous silicon strain during in situ ultrahigh vacuum thermal annealing

Abstract: In situ synchrotron radiation measurements of porous silicon (PS) strain have been performed during ultrahigh vacuum (UHV) thermal annealing. For a p+ sample, the initial lattice expansion shifts toward a contraction above 270 °C in relation with hydrogen desorption. For a p− sample, the strain variation is similar to that of a p+ one, but with effects five times larger: after hydrogen desorption, the contraction strain is large (>1.5%) and inhomogeneous. In both cases, most of these strains are elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 44 publications
6
34
1
Order By: Relevance
“…This result is in good agreement with numerous X-ray diffraction measurements [17] detecting relative increase of the lattice parameter z a a ∆ in the aged meso-PS samples up to 2×10 -3 compared to bulk Si. Such proximity of the macroscopic and sub-nanoscale strains can be explained by an elastic nature of the inter-atomic distance increase induced by the nanoscale porosification of bulk Si and air storage of the formed porous nanostructures.…”
Section: Stress and Strain In As-prepared Meso-ps Layersupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in good agreement with numerous X-ray diffraction measurements [17] detecting relative increase of the lattice parameter z a a ∆ in the aged meso-PS samples up to 2×10 -3 compared to bulk Si. Such proximity of the macroscopic and sub-nanoscale strains can be explained by an elastic nature of the inter-atomic distance increase induced by the nanoscale porosification of bulk Si and air storage of the formed porous nanostructures.…”
Section: Stress and Strain In As-prepared Meso-ps Layersupporting
confidence: 92%
“…Such proximity of the macroscopic and sub-nanoscale strains can be explained by an elastic nature of the inter-atomic distance increase induced by the nanoscale porosification of bulk Si and air storage of the formed porous nanostructures. The origin of the initial strain is shown to be related to the presence of hydrogen (fresh PS) and/or oxygen (aged PS) covering the Si nanocrystallites surfaces [12,[17][18][19]. Indeed, H-terminated Si atoms situated at the nanocrystallites surfaces relax toward the formed nano-pores because (i) of the decrease of the binding energy of the surface Si atoms and (ii) of the mutual attraction between the hydrogen covered surfaces due to van der Waals forces [18].…”
Section: Stress and Strain In As-prepared Meso-ps Layermentioning
confidence: 99%
“…The lattice contraction was previously ascribed to the effect of hydrostatic pressure arising from surface stress [165] and the intrinsic compressibility of the material [154,166e168]. The central lattice expansion is expected to be the consequence of surface oxidation.…”
Section: Observations and Interpretationsmentioning
confidence: 99%
“…The average Si-Si bond length is found to be contracted compared to the bulk; the contraction is reduced and tends towards the bulk value as the size of the nanocrystal is increased. Looking at individual Si-Si bonds, it is found that the outer shell is contracted, which has been interpreted as due to surface stress, 63,64 61 In classical linear elasticity, inhomogeneities, whether in vacuo or embedded in a material, have size-independent elastic fields. 65 This is the result of neglecting surface energies which can be justified when the ratio of surface to volume atoms is small.…”
Section: Calibrationmentioning
confidence: 99%